Effects of Group-delivered Stress-reduction Guided Imagery on Salivary Cortisol, Salivary Amylase, and Stress Mood in Urban, Predominantly Latino Adolescents - Marc J. Weigensberg MD; Cheng K. Fred Wen PhD; Donna Spruijt-Metz PhD; Christianne Joy Lane PhD (SAGE Publishing, 2022)
Objectives To determine acute effects of stress-reduction guided imagery delivered in group format on stress biomarkers salivary cortisol and salivary amylase, and on self-reported stress mood, in healthy, predominantly Latino adolescents. Study Design 111 adolescent participants (94% Latino), a subset from a large, randomized controlled lifestyle intervention to improve obesity-related health behaviors, received either 4 weekly lifestyle education sessions (Lifestyle group; LS) or the same weekly lifestyle education sessions plus an additional weekly stress-reduction guided imagery session delivered in group format (Guided imagery group; GI). Salivary cortisol, salivary amylase, and self-reported stress moods were assessed before and after sessions on intervention weeks 3 and 4. Statistics: Linear mixed effects models examined within- and between-session and group differences in pre- to post-session changes. Results Both groups showed decreases in salivary cortisol, 5% decrease in LS group and 32% in GI group (within-group differences all P < .05), with between-group difference in salivary cortisol of moderate size ( P = .05; Cohen's d = .44). Within the GI group alone, salivary cortisol decrease was similar following either the lifestyle or GI sessions ( P = .64). There were no statistically significant amylase changes within or between groups. All 5 individual stress moods declined by 27% to 46% in the GI group (all P < .05), while only 1 of the 5 declined in LS group. Conclusions Group stress-reduction guided imagery reduces the stress biomarker salivary cortisol, as well as reducing subjective stress mood states, making it a viable modality for large scale stress-reduction interventions.